Optic atrophy 1 is an A-kinase anchoring protein on lipid droplets that mediates adrenergic control of lipolysis - Pidoux, Guillaume; Witczak, Oliwia; Jarnæss, Elisabeth; Myrvold, Linda; Urlaub, Henning; Stokka, Anne Jorunn; Küntziger, Thomas; Taskén, Kjetil (The EMBO journal, 2011)
Adrenergic stimulation of adipocytes yields a cAMP signal that activates protein kinase A (PKA). PKA phosphorylates perilipin, a protein localized on the surface of lipid droplets that serves as a gatekeeper to regulate access of lipases converting stored triglycerides to free fatty acids and glycerol in a phosphorylation‐dependent manner. Here, we report a new function for optic atrophy 1 (OPA1), a protein known to regulate mitochondrial dynamics, as a dual‐specificity A‐kinase anchoring protein associated with lipid droplets. By a variety of protein interaction assays, immunoprecipitation and immunolocalization experiments, we show that OPA1 organizes a supramolecular complex containing both PKA and perilipin. Furthermore, by a combination of siRNA‐mediated knockdown, reconstitution experiments using full‐length OPA1 with or without the ability to bind PKA or truncated OPA1 fused to a lipid droplet targeting domain and cellular delivery of PKA anchoring disruptor peptides, we demonstrate that OPA1 targeting of PKA to lipid droplets is necessary for hormonal control of perilipin phosphorylation and lipolysis. Adrenergic stimulation of adipoytes induces PKA‐dependent phosphorylation of perilipin, the major regulator of lipolysis in lipid droplets. The mitochondrial dynamics regulator Optic Atrophy 1 is the A‐kinase anchoring protein on lipid droplets, and is required for the regulation of lipolysis.